Relationship between inflammatory cytokines and self-report measures of training overload - Main, L. C.; Dawson, B.; Heel, K.; Grove, J. R.; Landers, G. J.; Goodman, C. (Research in Sports Medicine, 2010)
It has been purported that inflammatory cytokines may be responsible for the aetiology of overtraining. The aim of the present study was to investigate the relationship between self-reported measures of overtraining and inflammatory cytokines. Eight elite male rowers were monitored in their natural training environment for 8 weeks prior to the 2007 Rowing World Championships. During this period of intense endurance training, self-report measures of overtraining and inflammatory cytokines (Interleukin (IL)-1ß, IL-6, IL-8, IL-10, IL-12p70, and Tumor Necrosis Factor (TNF)-) were assessed fortnightly. Consistent with previous findings, proinflammatory cytokines IL-1ß and TNF- were significantly associated (p = 0.05) with measures of depressed mood, sleep disturbances, and stress. Similarly, IL-6 was significantly associated (p = 0.01) with measures of depressed mood, sleep disturbances, and fatigue. These results are consistent with previous hypotheses describing how overtraining may be caused by excessive cytokine release, and lend further support for a cytokine hypothesis of overtraining.